Thermal Conductivity of Geopolymer with Polypropylene Fiber. Issue 1 (January 2020) - Rastri Utami, Felisitas Aprilia; Triwiyono, Andreas; Agustini, Ni Komang Ayu; Perdana, Indra
Abstract: Geopolymer is widely used to replace cement for fire-resistant products. The benefits of geopolymer based on fly ash are cost-effective and easy process production. Lightweight products are needed to minimize dead load for the existing structure. The addition of polypropylene fiber is intended to produce relative lightweight and strong material applied for fire resistance. This research was conducted to obtain thermal conductivity, density, and compressive strength of the geopolymer. The ratio of activator/fly ash (a/f) was varied 40%, 45%, and 50% with addition of polypropylene fibers of 0.5%, 1%, and 1.5% of the fly ash weight. The experimental test was conducted on the 7th day at ambient temperature while concentration of NaOH used in geopolymer synthesis was kept at 10M with a ratio of alkaline activator (Na2 SiO3 /NaOH) of 2. The test results showed that thermal conductivity (λ) is in a range between 0.19-0.82 W/m.C while the thermal conductivity is less than 1 W/m.C. This indicates that the geopolymer can be applied for thermal insulating material. Geopolymer with polypropylene fiber and a/f 50% can be classified as lightweight material with a density around 1.6283-1.7625 gr/cm 3 . The ratio of a/f 50% produces a compressive strength ranging from 18.14 MPa to 28.42 MPa.